Distinct Microbial Community of Accumulated Biofilm in Dental Unit Waterlines of Different Specialties - Fan, Cancan; Gu, Haijing; Liu, Limin; Zhu, Haiwei; Yan, Juan; Huo, Yongbiao (Frontiers in Cellular and Infection Microbiology, 2021)
The contamination of dental unit waterlines (DUWLs) is a serious problem and directly affects the dental care. This study aims to explore the microbial community of biofilm in DUWL from different specialties and investigate the associated factors. A total of 36 biofilm samples from 18 DUWL of six specialties (i.e., prosthodontics, orthodontics, pediatrics, endodontics, oral surgery, and periodontics) at two time points (i.e., before and after daily dental practice) were collected with a novel method. Genomic DNA of samples was extracted, and then 16S ribosomal DNA (rDNA) (V3–V4 regions) and ITS2 gene were amplified and sequenced. Kruskal–Wallis and Wilcoxon rank test were adopted for statistical analysis. Microbial community with high diversity of bacteria (631 genera), fungi (193 genera), and viridiplantae was detected in the biofilm samples. Proteobacteria was the dominant bacteria (representing over 65.74–95.98% of the total sequences), and the dominant fungi was Ascomycota (93.9–99.3%). Microorganisms belonging to multiple genera involved in human diseases were detected including 25 genera of bacteria and eight genera of fungi, with relative abundance of six genera over 1% (i.e., Acinetobacter, Pseudomonas, Enterobacter, Aspergillus, Candida, and Penicillium). The biofilm microbiome may be influenced by the characteristics of dental specialty and routine work to some extent. The age of dental chair unit and overall number of patients had the strongest impact on the overall bacteria composition, and the effect of daily dental practices (associated with number of patients and dental specialty) on the fungi composition was the greatest. For the first time, biofilm in DUWL related to dental specialty was comprehensively evaluated, with more abundance of bacterial and fungal communities than in water samples. Biofilm accumulation with daily work and multiple kinds of opportunistic pathogen emphasized the infectious risk with dental care and the importance of biofilm control.